2023
DOI: 10.5267/j.ijdns.2022.8.009
|View full text |Cite
|
Sign up to set email alerts
|

Integrated e-learning for knowledge management and its impact on innovation performance among Jordanian manufacturing sector companies

Abstract: E-learning in knowledge management was examined in this study, specifically on how it assists organizations in improving knowledge transfer and e-learning management, to increase performance and employee knowledge management. In this study, e-learning and knowledge management systems and technology were jointly implemented, and its impact on organizational performance was examined. Organizational management was also explored. The present study investigated the relationship between knowledge management (KM) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Numerous studies have demonstrated that the integration of E-learning methodology yields positive and statistically significant effects on students' academic advancement (Elfaki et al, 2019;Mothibi, 2015;Abooki and Kitawi, 2014;Basri et al, 2018;Salamat et al, 2018). The findings consistently indicate that the utilization of E-learning approaches within higher education institutions leads to improved academic achievements among students and it is also discovered that e-learning is a positive idea in Pakistan (AL-Sous et al, 2023). Additionally, the results of this study addressed all the objectives and hypotheses are approved.…”
Section: Discussionsupporting
confidence: 60%
“…Numerous studies have demonstrated that the integration of E-learning methodology yields positive and statistically significant effects on students' academic advancement (Elfaki et al, 2019;Mothibi, 2015;Abooki and Kitawi, 2014;Basri et al, 2018;Salamat et al, 2018). The findings consistently indicate that the utilization of E-learning approaches within higher education institutions leads to improved academic achievements among students and it is also discovered that e-learning is a positive idea in Pakistan (AL-Sous et al, 2023). Additionally, the results of this study addressed all the objectives and hypotheses are approved.…”
Section: Discussionsupporting
confidence: 60%
“…This will eventually lead to increasing their participation in innovative behaviors, which might be beneficial to the organization. They are represented in linking their personal objectives with the objectives of the organization and striving to achieve the healthy development of the organization by taking risks as well as trial and error to reach to new ideas contributing to developing the performance of their organizations and increasing their ability to compete (Chen & Aryee, 2007;Rank et al, 2009;Wu, 2019;Wen et al, 2021;AL-Sous et al,2023). Thus, we can conclude that ethical leadership indirectly supports the innovative behavior of employees through organizational commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Firms are more interested in cultural elements of company behavior over the remaining organizational behavior components, which was the strongest effect (Hanaysha, 2016). According to Peter and Waterman (1982), a company's culture is crucial to its performance (AL-Sous et al, 2023). It was suggested for administrators to handle their duties by adhering to their company culture, that helps to rise through the growth in the company, and in numerous business journals along with business documents, released 57 frequently asserted that culture was essential to the company's achievement (Moorhead & Griffin, 1995).…”
Section: Introductionmentioning
confidence: 99%